Mandatory universal use of cloth mask for prevention of coronavirus disease 2019 transmission - Yenny, Yenny; Herwana, Elly; Wratsangka, Raditya (Faculty of Medicine, Universitas Trisakti, 2021)
Since the outbreak in Wuhan City, China, in late December 2019, the Coronavirus Disease 2019 (COVID-19) has spread to nearly the whole world, so that it was declared a pandemic by the Word Health Organization. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative organism of COVID-19, is extremely infectious and can adhere to droplet nuclei of < 5 mm diameter and become airborne (aerosol). Since COVID-19 was declared a pandemic, there has been controversy on the use of cloth masks by the public, because of the still inconclusive evidence of the efficacy of cloth masks in protecting against COVID-19 transmission. Universal masking as a healthcare intervention in the community is currently made mandatory by local governments of most countries, since they follow the recent recommendation by the World Health Organization. The issuing of the WHO recommendation on the public use of masks was based on a study demonstrating that COVID-19 transmission does not occur only through droplets but also through aerosols. In addition, there was a study showing that COVID-19 transmission does not only occur from patients with clinical symptoms but also through asymptomatic and pre-symptomatic subjects, so that universal masking is of benefit in providing protection when used by healthy people and as source control to prevent cross-transmission to other people. This review article aims to discuss the mechanism of COVID-19 transmission, the evidence related to the efficacy of cloth masks, and the guidelines related to the selection and use of masks by the general population.